Networks of New Actors in Knowledge Space of Education and Educational Psychology in Modern Thai Society - Nasee, Pisith; Nawarat, Nongyao; Jatuporn, Omsin; Sapphasuk, Wasan (Journal of Social Sciences Naresuan University, 2025)
This article explores the formation and practices of new actors in knowledge space of education in Thailand through four case studies: Thai Civic Education (TCE), Kor Karn Kru, insKru, and Kru Kor Sorn. The study focuses on how these groups generate alternative educational knowledge, reconstruct the identity of teachers, and create participatory learning spaces grounded in critical thinking and lived experiences of both teachers and learners. Using qualitative research methods-including document analysis, in-depth interviews, focus group discussions, and observation. This research investigates the relationships among educational structures, learning processes, and the grassroots movements that challenge existing systems. By applying Melucci’s concept of New Social Movements (NSM), the study finds that these groups do not only seek educational reform but also function as cultural movements with distinctive characteristics. These include the processual construction of collective identity, horizontal network structures, the use of digital technology and everyday life as platforms for action, and the co-production of knowledge that questions dominant institutional power. The article argues that both the state and Thai society should recognize the importance of building a participatory knowledge ecology that opens space for civic-based actors and new networks to engage meaningfully in shaping the future of education. Such an approach is vital for advancing educational reform rooted in culture, lived experience, and democratic values.